2007
DOI: 10.1271/bbb.60420
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SalivaryLactobacillusandBifidobacteriumSpecies in Periodontal Health and Disease

Abstract: We surveyed the distribution of salivary Lactobacillus and Bifidobacterium species in periodontitis patients and healthy subjects. Approximately 700 lactobacilli and 300 bifidobacterial isolates were obtained from 16 young, orally healthy subjects (mean age +/- standard deviation: 21.0+/-2.0 y), 16 periodontitis patients (51.6+/-13.8 y), and 14 well-maintained former periodontitis patients (60.2+/-9.6 y). Among eleven Lactobacillus species detected in saliva, L. salivarius, L. gasseri, and L. fermentum were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
(36 reference statements)
2
46
0
2
Order By: Relevance
“…In figure (3) we compare between group A(chewing gum) and group B(control) , the chewing gum patient show slightly higher decrease in in plaque index and gingival index between the first and second week than the controlled patient ,this agree with (Hojo et al,2007). In table 5 shown that there are significant deference between two group and that agree with many research that the probiotic can defense the bacterial plague and enhance the oral hygiene which is the ability of lactobacillus acidophilus to fight the biofilm in oral cavity.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In figure (3) we compare between group A(chewing gum) and group B(control) , the chewing gum patient show slightly higher decrease in in plaque index and gingival index between the first and second week than the controlled patient ,this agree with (Hojo et al,2007). In table 5 shown that there are significant deference between two group and that agree with many research that the probiotic can defense the bacterial plague and enhance the oral hygiene which is the ability of lactobacillus acidophilus to fight the biofilm in oral cavity.…”
supporting
confidence: 74%
“…The use of probiotic chewing gum containing L. reuteri ATCC 55730 and ATCC PTA 5289 also and Use of tablets containing L. salivarius WB21 has been shown to decrease gingival pocket depth, particularly in high-risk groups such as smokers, and also affect the number of periodontontalpathogens in plaque. 7,8 Again, although encouraging results have been observed, most studies have been fairly short. Furthermore, in some studies the observed differences were quite small, though statistically significant.…”
mentioning
confidence: 99%
“…1 It is an autochthonous microorganism that colonizes the human mucosa, including the oral cavity, vagina, and gastrointestinal tract (GIT) in healthy individuals. [2][3][4][5][6][7] L. gasseri is also among the predominant microorganisms in the initial colonization of the neonatal GIT following childbirth. 8 Niche-related phenotypes have been defined that likely confer its capacity to colonize the mucosa and potentially contribute to the ability of L. gasseri to positively impact health.…”
Section: Introductionmentioning
confidence: 99%
“…Number of plasmid in the genome 5 Number of IS family that IS elements from the relevant Lactobcillus genome belong to 6 Number of intact prophage in the corresponding Lactobacillus genome 7 Number of genes that encoding cholyglycine hydrolase (EC 3.5.1.24) 8 Number of genes that encoding sortase 9 Number/type of intact restiction-modification system in the relevant Lactobcillus genome Abbreviations: 1 the C subunit of the tetanus toxin, 2 green fluorescent protein…”
mentioning
confidence: 99%